Food fertiliser (food waste composter) / Mohd Asyraf Dziaudin - Dziaudin, Mohd Asyraf (Universiti Teknologi MARA, Kedah, 2018)
We are producing solid waste in daily aftivities and this study focusing in food waste management from household. How household can reuse their daily food waste?. In this research, stated the data staticstic base on my current issues. My achieve toward helping the household with zero food wasted by providing composting product solutions. My goal is to help 'close the loop' of sustainability, allowing the food waste that comes from the farms to go back to the farms as fertiliser for future food. Waste can't be classify as pollution if we as socialty know how to manage our own waste. Food waste with proper disposal and by using composters will creates a valuable fertiliser to nourish our mother earth. In Al-Qu'ran syas: Indeed, wasteful are brothers of devils, and ever has satan been his Lord ungrateful. (al-israa:27).